2017
DOI: 10.1039/c7sc01672g
|View full text |Cite
|
Sign up to set email alerts
|

Interdomain flip-flop motion visualized in flavocytochrome cellobiose dehydrogenase using high-speed atomic force microscopy during catalysis

Abstract: To visualize the dynamic domain motion of class-I CDH from Phanerochaete chrysosporium (PcCDH) during catalysis using high-speed atomic force microscopy, the apo-form of PcCDH was anchored to a heme-immobilized flat gold surface that can fix the orientation of the CYT domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…Structures of the separate domains of P. chrysosporium CDH ( Pc CDH) were published in the early 2000s (CYT CDH : 1.9 Å, PDB 1D7C, (Hallberg et al 2000 ); DH CDH : 1.5 Å, PDB 1KDG, (Hallberg et al 2002 )), while structures of intact CDH were published only recently ( Neurospora crassa CDH IIA: 2.9 Å, PDB 4QI7; Myriococcum thermophilum CDH: 3.2 Å, PDB 4QI6), due to the difficulties in obtaining suitable crystals of the flexible proteins (Tan et al 2015 ). Harada et al recently confirmed the domain movement by using atomic force microscopy (Harada et al 2017 ). This conformational change and the mobility of the two domains are of particular importance for the electron transfer chain described below.…”
Section: Introductionmentioning
confidence: 90%
“…Structures of the separate domains of P. chrysosporium CDH ( Pc CDH) were published in the early 2000s (CYT CDH : 1.9 Å, PDB 1D7C, (Hallberg et al 2000 ); DH CDH : 1.5 Å, PDB 1KDG, (Hallberg et al 2002 )), while structures of intact CDH were published only recently ( Neurospora crassa CDH IIA: 2.9 Å, PDB 4QI7; Myriococcum thermophilum CDH: 3.2 Å, PDB 4QI6), due to the difficulties in obtaining suitable crystals of the flexible proteins (Tan et al 2015 ). Harada et al recently confirmed the domain movement by using atomic force microscopy (Harada et al 2017 ). This conformational change and the mobility of the two domains are of particular importance for the electron transfer chain described below.…”
Section: Introductionmentioning
confidence: 90%
“…The biggest contribution to binding comes from the electrostatic interaction of a haem propionate‐A group interacts with an Arg residue on the dehydrogenase domain on the side of the substrate channel . High‐speed atomic force microscopy was used to visualize the dynamic domain motion of P. chrysosporium CDH . An flip‐flop motion was observed involving domain‐domain association in the presence of the substrate cellobiose and subsequent dissociation, whereas the two domains were immobile in the absence of substrate.…”
Section: Direct Electrochemistry Of Flavocytochromesmentioning
confidence: 99%
“…In ar ecent paper,H arada et al exploitedh ighspeed atomicf orce microscopy to measure in operando the conformational changes of the cellobiosed ehydrogenase immobilized on flat gold surfaces functionalized with heme groups. [42] This work sheds light on the mechanism of this multi-domain protein at nanometric scale. The highly specialized infrastructure required for these studies makes that spatial resolution studies monitoring the catalytic activity of the immobilized enzymes are dominated by fluorescence spectroscopy;aworldwide and highly accessible technique.…”
Section: Single-particle Reaction Kinetics Of Immobilized Enzymesmentioning
confidence: 90%
“…In a recent paper, Harada et al. exploited high‐speed atomic force microscopy to measure in operando the conformational changes of the cellobiose dehydrogenase immobilized on flat gold surfaces functionalized with heme groups . This work sheds light on the mechanism of this multi‐domain protein at nanometric scale.…”
Section: Single‐particle Reaction Kinetics Of Immobilized Enzymesmentioning
confidence: 99%